Produtividade da soja com desfolha artificial em diferentes estádios fenológicos - Lacerda, Klinsmann Lima (2023)
Soybean leaf area is related to photosynthesis and therefore has a high correlation with productivity and stresses are important factors that reduce it, such as defoliation caused by hail or insects. The leaf area is also dependent on the characteristics of the cultivars, such as the cycle and their physiology and climatic conditions for plant development. Thus, the objective of this work was to determine the effects of defoliation at different phenological stages on the productivity of two soybean cultivars. For this, two experiments were set up with soybean cultivars M5947 IPRO and M6410 IPRO with different cycles and two artificial defoliations (33% and 66%) the 33% defoliation was carried out by removing one leaflet from each leaf of the plant and the 66% defoliation was carried out by removing two leaflets. were carried out manually at the phenological stages of V5, R1, R3 and R5. Each experiment was conducted in randomized blocks with three replications and plots of four rows five meters long and spaced 0.50 cm apart. The experiments took place in climatic conditions of low precipitation and high temperatures typical of the region, therefore, the environment was not suitable for the optimal development of the plants. There was a significant interaction between defoliation and phenological stages for each cultivar, indicating that the effect of defoliation on productivity depended on the intensity and at which phenological stage it occurred. For cultivar M5947 IPRO, 33% defoliation did not affect productivity and 66% defoliation affected productivity in the reproductive stages with greater intensity in the R3 stage, reducing productivity by an average of 25%. For cultivar M6410 IPRO, 33% defoliation affected productivity at the V5 stage and 66% defoliation affected it at the R5 stage. It can be concluded that soybean productivity reduces with defoliation to a greater or lesser extent depending on the phenological stage that occurs and is also dependent on the degree of relative maturity of the cultivar and aggravated by unfavorable climatic conditions. Keywords: Leaf Area. Soybean. Defoliate. Productivity. Row crop.